Assédio moral no ambiente de trabalho: estudo com enfermeiros de unidades de pronto atendimento - Rolim, Renata Maria Guedes Chaves (2019)
Introduction: The moral harassment is a type of violence capable of entailing physical and psychic health implications in its victims. This dissertation is composed of two articles. Article 1- Implications of moral harassment in the health of the nursing worker: integrative revision of the literature. Objective: Characterize the publications available in online periodicals about the implications of moral harassment on the health of the nursing worker with emphasis on the approaches addressed. Method: Integrative review of the literature, with samples constituted by 20 publications in Portuguese, English and Spanish, available in national and international databases, in the period from 2000 to 2018. Results: This study evidenced a reduced number of publications about the subject researched. The greater number of studies that composed the sample were performed in the hospital setting with nurses and nursing technicians. According with the approaches, two categories emerged: ―Implications of moral harassment in the psychological health of the nursing worker‖ and ―Implications of moral harassment in the physical health of the nursing worker‖. The main implications presented were: anxiety, fear, depression, stress, posttraumatic stress disorder (PTSD), mental exhaustion, Burnout syndrome, muscular and articular pain, digestive disorders, migraine and headache, bringing emotional, social and family disorders to the nursing worker victim of the harassment. Conclusion: This revision extended the knowledge about the subjective moral harassment and its implications for the nursing worker‘s health, evidencing that this violence occurs frequently in the work environment of the nursing workers, resulting in physical and psychic damages. All things considered, it is suggested that preventive measures be taken to banish this practice in the workplace. Article 2 – Moral harassment in the workplace: study with nurses of emergency care units. Objective: Identify the practice of moral harassment in the workplace from statements of nurses that work in emergency care units; analyze statements of nurses that work in emergency care units about the practice of moral harassment in the workplace in the light of pertinent literature to the theme being studied. Method: Study exploratory with qualitative approach. Collection of data realized by means of the interview technique with semi-structured instrument. A total of 30 nurses that work in emergency care units in the city of João Pessoa, Paraiba – Brazil, participated in the study with the approval of the ethical committee in research. Results: There were relevant elements that characterize the moral harassment like duration and frequency of the aggressions, such as life experiences reports and implications of the moral harassment in the victim‘s health. Psychopathological symptoms were observed as consequences of moral harassment to the health of nurses, such as stress, crying crisis, low self-esteem, depression, sadness and the most prevalent psychosomatic symptoms were insomnia and obesity. Conclusion: Moral harassment situations were identified in the workplace of emergency care unit nurses that caused serious repercussions in the health of nursing workers victims of the practice referred to above. Therefore, there has to be a greater disclosure of this phenomenon, with emphasis on the forms of prevention and coping with this violence.